RANCANG BANGUN APLIKASI SKRINING KESEHATAN MENTAL REMAJA BERBASIS WEB DI RSUD DR.DRADJAT PRAWIRANEGARA DENGAN MENGGUNAKAN METODE ANALYTIC HIERARCHY PROCESS (AHP) - Sutanto Sutanto; Dadang Amiruddin; Gagan Nugraha (Journal of Innovation And Future Technology (IFTECH), 2022)
The development of information systems is now very fast and rapid, one form of information system that is easy to develop is web-based. The use of information systems in the medical world is very much, but there are still some who have not utilized the information system to help the work of a medical worker, especially in helping the development of mental health. The system used to help improve mental health in dr.Dradjat Prawiranegara Hospital is now still conventional, namely face to face between medical personnel and patients, this is what makes teenagers who have problems with their mental health have a variety of reasons not to visit a psychiatrist. The web-based adolescent mental health screening application is designed using php programming language, MySQL database and decision making system using Analytic Hierarchy Process (AHP) method. By implementing Web- Based Adolescent Mental Health Screening Application Using Analytic Hierarchy Process (AHP) method is expected to help teenagers know their mental health independently and provide information and education about mental health disorders.